Image acquisition system for agricultural context-aware computing - Boxiang, Xiao; Chuanyu, Wang; Xinyu, Guo; Sheng, Wu (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Context-aware computing is a new mode originated from ubiquitous computing. Its emergence brings a substantial change to traditional computing and related service. Image is a pervasive tool for context awareness. A large number of applications are developed based on images analysis. In this paper, an image acquisition system is presented for agricultural context-aware computing. The potential use of the system includes production evaluation, precise management and assistant control. The system includes four modules: the camera system, the control system, mechanism, and communication. The system can be easily installed in target crop fields. The camera system is composed of a binocular stereo camera and a color camera. Two cubic images and a corresponding texture image are collected for each plant in the process of data acquisition. An accessorial software system is developed to control and manage the capture system. Experiments show that the presented system is effective for image acquisition of agricultural context-aware computing.Keywords: image acquisition, agriculture, context-aware computingDOI: 10.3965/j.ijabe.20140704.008Citation: Xiao B X, Wang C Y, Guo X Y, Wu S. Image acquisition system for agricultural context-aware computing. Int J Agric & Biol Eng, 2014; 7(4): 75－80.